Integrating indigenous perspectives for the study of the maritime cultural landscapes in the Colombian Caribbean: an ancestral approach to the nautical space of the San José Galleon - Del Cairo Hurtado, Carlos; Izquierdo Mejía, Diomedes; Aldana Mendoza, Jesús Alberto; Quintero Hernández, Juliana; Sarmiento Rodríguez, Juan David; Báez Santos, Laura Victoria; Reina Martínez, Carlos Andrés (Frontiers in Environmental Archaeology, 2026)
In recent years, Colombia has implemented new conceptual, theoretical, and interpretive approaches to understanding past and, therefore, contemporary human dynamics in its scientific projects on maritime and underwater archaeology. This discipline is relatively new in the country, having developed over the past three decades. However, significant progress has been made in staff training, capacity building, and applying new methods that enhance the comprehension of maritime archaeological sites. One example is indigenous archaeologies, whose approaches and analytical contributions have recently been applied to shipwrecks and their associated contexts, including terrestrial, coastal, and underwater sites. The goal of this article is to present and discuss recent research advances in Indigenous Maritime Archaeology in the Colombian Caribbean. Particular attention is given to how this field has contributed to a more comprehensive understanding of nautical spaces from an ancestral perspective, with a focus on the San José galleon, which sank on 8 June 1708. These environments are understood as places where everything related to boats occurs. Thus, they are not limited or conditioned solely by ships as objects or only the materiality itself. For it is there where human and natural (or physical) elements come together in the configuration of this landscape.